Caries Management and Vertical Dimension Modification Using Stainless Steel Crowns in Pediatric Patients with Multiple Carries: Case Reports - Rima Nur Lesmanawati; Naninda Berliana Pratidina (International Journal Labs, 2026)
Dental caries is the most common chronic oral disease in children and remains the leading cause of tooth structural loss. In the case of some caries, extensive destruction can result in a reduction in the vertical dimensions of the occlusion, which can negatively impact chewing, speech, aesthetics, and even craniofacial development. Therefore, a comprehensive management strategy is essential, combining caries elimination, dental restoration, and occlusal rehabilitation. Stainless Steel Crown (SSC) is considered a reliable restorative material in pediatric dentistry due to its durability, full-coverage protection, and ability to reconstruct occlusal vertical dimensions. This case report aims to describe the management of multiple caries in pediatric patients using SSC as a definitive restoration and tool for vertical dimension modification. A 5-year-old girl was presented with some caries involving several primary molars, accompanied by a decrease in vertical dimensions. Clinical and radiographic evaluation confirmed extensive carius lesions. Treatment involves caries removal and pulp therapy on the indicated tooth, followed by the placement of SSCs on the severely affected molars. SSC restoration successfully restored occlusal contact and corrected the loss of vertical dimensions. The use of SSC in this case not only provides long-term protection for the primary caryrius molars but also restores occlusal balance through vertical dimensional adjustment. This results in improved chewing, patient comfort, and functional stability with no reported complications. SSC thus has the dual role of a restorative solution and a tool for occlusal rehabilitation. SSC is an effective treatment modality in pediatric patients with multiple caries, offering structural preservation and modification of vertical dimensions. Its application supports optimal oral function, comfort, better eating behavior, and weight gain.